Effects of a single protruded rectangular feature on a circular cylinder - Chai, Zhong Rong (2016)
Large Eddy Simulation (LES) is performed on a numerical investigation to study the effects of an introduction of a rectangular protruded feature on a single circular cylinder, subjected to a flow of Reynolds number, Re = 10^5. The effects on vortex shedding, pressure distribution, drag and lift forces are discussed in this study. These results are compared to smooth circular cylinders without protrusion. In this geometry configuration, it was found that vortex shedding can be suppressed though a slight increase in drag force. This research can prove to be useful for marine and wind engineering applications.